Determinants of Low Back Pain (LBP) Complaints among Garbage Truck Drivers - Anggara, Arie; Novrikasari, Novrikasari; Windusari, Yuanita; Bin Yusof, Muhammad Safwan; Haidir, Hala; Syafaruddin, Syafaruddin; Hasyim, Hamzah; Noviadi, Pitri (Poltekkes Kemenkes Tanjung Karang, 2023)
Low back pain (LBP) is one of the musculoskeletal disorders with the highest intensity in truck drivers. LBP is a work-related disorder that is one of the leading causes of activity limitations, disability, inability to work, and absence from work. This research analyzes the determinants of LBP complaints among garbage truck drivers. The method used a cross-sectional approach. The respondents in this study were garbage truck drivers at TPA Sukawinatan in Palembang City, with a sample size of 76 drivers taken by purposive sampling. The research results showed that there was a significant correlation between exercise habits (p-value = 0.024), work period (p-value = 0.041), driving duration (p-value = 0.011), and complaints of LBP among garbage truck drivers. There was no significant correlation between age (p-value = 0.762), smoking status (p-value = 0.915), and job satisfaction (p-value = 0.648) with complaints of LBP among garbage truck drivers. The conclusion showed that LBP complaints among garbage truck drivers were reported by 52 respondents (68.4%). Exercise habits, work period, and driving duration were significant determinants of LBP complaints among garbage truck drivers at the TPA Sukawinatan.